Relacionando o comprometimento organizacional e a responsabilidade social corporativa - Mortati, Isabella Borghi (2009)
Competitiveness and social responsibility have been constantly discussed at the academic and economic environment. On one side, companies pursue competitiveness through efficiency, excellence and constant performance improvement. This performance, as mentioned by Bateman and Strasser (1984), finds among its groundings the employees’ commitment to their organization. On the other side, society, and all its agents, demands in an each time stronger and broader manner that companies act in socially responsible ways. Therefore the present work aimed to analyze an organizational commitment model and a corporate social responsibility one, that would provide the foundations for understanding both concepts and the possible relations between them. Four interest groups to which corporate social responsibility can be intended – social and non social stakeholders, employees, customers and government – and three dimensions of organizational commitment – affective, normative and continuance – were obtained. Through correlation and regression analysis, it was found that, for the given sample, the corporate social responsibility actions aimed to employees and to customers have a positive relation with affective and normative commitments, while the corporate social responsibility actions aimed to social and non social stakeholders and to the government have a direct relation only to the affective commitment. Further relations between the dependent and independent variables were found absent. Thus, this work proposes that managers, aware of the possible valuable effects on the employees’ organizational commitment and thereafter results and performance, act in order to clarify and improve employees’ perception about corporate social responsibility activities. Besides deepening the knowledge about the causes and antecedents of organizational commitment, it is believed that the results demonstrated may guide organizations in their conscience improving actions on corporate social responsibility in a more effective way.